The Influence of Jawa Post Publication and Group Involvement towards Public Participation in Surabaya Green And Clean (SGC) Program - Noorshanti Sumarah (Sekolah Pascasarjana Universitas Brawijaya, 2016)
Environmental development in Surabaya is carried out through various programs inviting the public to participate in them. â€œSurabaya Green and Cleanâ€ is one of the programs. It involves the public and Jawa Post, a national newspaper, as a means to spread information. The study aims at testing the influence of publication and group involvement towards public participation in the program. Based on the hypothesis testing, it is concluded that publishing news about â€œSurabaya Green and Cleanâ€ in Jawa Post and group involvement have significant influence towards public participation in â€œSurabaya Green and Cleanâ€ Program.